Influência dos carboidratos e da expressão de genes relacionados à parede celular na floculação de saccharomyces cerevisiae - Santos, Renan Vasconcelos (2013)
Since the dawn of civilization, man has used microbial fermentation to produce various consumer goods. The yeast Saccharomyces cerevisiae is undoubtedly the main factor in known fermentation processes, responsible for the production of bread, beer, wine, cachaça and bioethanol. S. cerevisiae was the first eukaryotic organism to have its genome sequenced and has been used for several decades as a model for eukaryotic cellular and molecular studies. The yeast cell wall is a robust structure composed of a structural internal layer of glucan and chitin, and an outer layer of mannoproteins covalently linked to the structural layer, which determine the bulk properties of the cell surface. The flocculation of yeast can be defined as a non-sexual, reversible and calcium-dependent aggregation of cells in multicellular masses, called flocs, with subsequent sedimentation from the medium in which they are suspended. It is a very complex process and depends on numerous factors such as the characteristics of the medium (pH and the presence of cations), conditions of fermentation (oxygenation, sugars, growth temperature, and the ethanol concentration) and the expression of genes of the FLO family. The process involves the interaction of specialized cell wall proteins called lectins, present only in cell flocculants, and carbohydrates (receptors) in the cell wall of neighboring cells. Flocculation properties specifically set may lead to an improvement in the processing of fermentation biotechnology products, such as food, beverages and biofuels. The group s previous data on the identity of flocculation profile between wild yeast strains isolated from different stills showed two strains with a characteristic profile of sedimentation (BT0510 BT0605), while two others (BT0505 and BT0601) showed no flocculation capacity. The objective of this study was to evaluate the relationship between the content of carbohydrates (glucose and mannose) and cell wall-related genes to the flocculation process in order to better understand the factors that cause the difference in behavior flocculant. Yeast cells were grown in YEPD medium and incubated at 28 ° C and 150 rpm agitation. The cell wall was extracted by a combination of sonication, vigorous agitation with glass beads and boiling in detergent solution. After extensive washing with ultrapure water, the pellet containing the cell wall was incubated at 80 ° C to complete drying and determination of dry weight. Then the samples were subjected to hydrolysis with sulfuric acid, precipitation of sulphate ions by adding Ba (OH) 2, and concentration in vacuum. The liberated monosaccharides were analyzed by HPLC on a column of REZEX-RHM, isocratic elution with ultrapure water, differential refraction detector at 60 ° C. The expression levels of FLO genes and genes related to cell wall between a flocculent strain and a non-flocculent were compared using Real Time PCR. No significant difference was found between the levels of glucose and mannose in flocculent and non-flocculent strains, which suggests that the profile of flocculation is not directly related to the concentration of cell wall carbohydrates. Analysis of relative gene expression showed a significant increase in the FLO gene family (FLO1, FLO8 and FLO10) in flocculant strain, confirming expectations. A large increase of 27 times was noted in CWP1 gene, confirming studies suggesting a major importance of this gene for the cell wall and in the flocculation process. There was also an increase in other genes related to the cell wall. Studies of cell wall proteomics, and mass spectrometry analysis may help elucidate the results, and contribute to a better understanding of flocculation in fermentation processes.